2019
DOI: 10.9734/jsrr/2019/v24i530163
|View full text |Cite
|
Sign up to set email alerts
|

An Opinion Regarding Equivalence Testing for Evaluating Measurement Agreement

Abstract: The novel statistical approach 'equivalence testing' has been proposed in order to statistically examine agreement between different physical activity measures. By using this method, researchers argued that it is possible to determine whether a method is significantly equivalent to another method. Recently, equivalence testing was supported with the use of 90% confidence interval, obtained from a mixed ANOVA, which I believe is a more robust approach. This paper further discusses the use of this method in comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Further, both fixed and proportional bias, as well as unacceptably high MAPE were found, suggesting a lack of agreement between the two devices on an individual level, similar to previous findings relating to the accuracy of EE estimates from wearable devices (Shei et al., 2022). This divergence in the assessment of agreement is not unexpected as the statistical methods used assess different components of agreement (group‐level vs. individual‐level) (Adamakis, 2019), but does highlight the need to interpret the results of studies investigating the validity of wearable devices carefully. Of note in this study, the MAPE of 11.3% for the Apple Watch, which was the lowest of the devices tested in this study, was similar to the error found in other studies using protocols of fast walking or running, and substantially lower than the MAPE reported in studies estimating EE at rest.…”
Section: Discussionmentioning
confidence: 99%
“…Further, both fixed and proportional bias, as well as unacceptably high MAPE were found, suggesting a lack of agreement between the two devices on an individual level, similar to previous findings relating to the accuracy of EE estimates from wearable devices (Shei et al., 2022). This divergence in the assessment of agreement is not unexpected as the statistical methods used assess different components of agreement (group‐level vs. individual‐level) (Adamakis, 2019), but does highlight the need to interpret the results of studies investigating the validity of wearable devices carefully. Of note in this study, the MAPE of 11.3% for the Apple Watch, which was the lowest of the devices tested in this study, was similar to the error found in other studies using protocols of fast walking or running, and substantially lower than the MAPE reported in studies estimating EE at rest.…”
Section: Discussionmentioning
confidence: 99%